2017
DOI: 10.1159/000481532
|View full text |Cite
|
Sign up to set email alerts
|

New Diagnostic Criteria of Polycystic Ovarian Morphology for Adolescents: Impact on Prevalence and Hormonal Profile

Abstract: Background: The ultrasonographic criteria used to identify polycystic ovarian morphology (PCOM) during adolescence have changed over time. Recently, a Worldwide Pediatric Consensus (PedC) defined PCOM using stricter criteria than the previous recommendations of the Rotterdam Consensus (RC) and Androgen Excess-Polycystic Ovarian Syndrome Society (AES/PCOS) criteria. The aim of this study was to determine the prevalence of PCOM in healthy adolescents according to the 3 reported diagnostic criteria and compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…In 2015, the World Pediatric Consensus (PedC) suggested the possibility of using the AMH level as a non-invasive screening test for PCOS diagnosis [11]. Yetim et al calculated cut-off for the AMH for 15-20 years old youth with PCOS and showed that AMH value > 6.10 ng/mL had 92.3% sensitivity and 81.1% specificity in the diagnosis [2].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2015, the World Pediatric Consensus (PedC) suggested the possibility of using the AMH level as a non-invasive screening test for PCOS diagnosis [11]. Yetim et al calculated cut-off for the AMH for 15-20 years old youth with PCOS and showed that AMH value > 6.10 ng/mL had 92.3% sensitivity and 81.1% specificity in the diagnosis [2].…”
Section: Discussionmentioning
confidence: 99%
“…Yetim et al calculated cut-off for the AMH for 15-20 years old youth with PCOS and showed that AMH value > 6.10 ng/mL had 92.3% sensitivity and 81.1% specificity in the diagnosis [2]. The research based on examining of 102 adolescents with PCOS, conducted by Merino et al, recommended the threshold for AMH > 7.03 ng/mL with 50.0% sensitivity and 70.8% specificity [11]. Though such investigations in adolescence are rare, according to our results, the use of AMH levels > 7.20 ng/mL with high sensitivity and specificity (75.0% and 89.0%) could be one of the perspective diagnostics tests of PCOS in girls at the age of 15-17 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, there is disagreement about the definition of polycystic-appearing ovaries in the adolescent population. The Rotterdam criteria use ovarian volume greater than 10 mL or more than 12 follicles on an ovary using a vaginal transducer, however, adolescents have been noted to have greater ovarian volumes and follicular counts than adult women, and it is not recommended to perform vaginal ultrasound on this population [ 6 , 10 , 11 ]. In a retrospective study, only 38% of adolescents who met Rotterdam criteria for PCOS had ovarian volumes ≥10 mL, while 7% of a comparison non-PCOS population had ovarian volumes ≥10mL [ 12 ].…”
Section: Introductionmentioning
confidence: 99%